If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12x-4x^2=-24
We move all terms to the left:
12x-4x^2-(-24)=0
We add all the numbers together, and all the variables
-4x^2+12x+24=0
a = -4; b = 12; c = +24;
Δ = b2-4ac
Δ = 122-4·(-4)·24
Δ = 528
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{528}=\sqrt{16*33}=\sqrt{16}*\sqrt{33}=4\sqrt{33}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(12)-4\sqrt{33}}{2*-4}=\frac{-12-4\sqrt{33}}{-8} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(12)+4\sqrt{33}}{2*-4}=\frac{-12+4\sqrt{33}}{-8} $
| 1x=2000 | | x+18*10/100=35 | | 32=2.72^(5k) | | x8(x+7)=−96 | | 135=-16t^2+169T+100 | | (1-3x)/(2x)=0 | | 10(3–x)=20 | | 1/x+1/x^2=3/4 | | x+10/2=15 | | y+6=50 | | 47+x=-23 | | (3x-1/3)-(x/2-5/3)+6-1/2=14/3 | | 7x-4+(3x+15-18x)/3=(8x+4+16x)/4-13x-(8+2x+12)/2+x+1 | | 7y^2+6y+5=0 | | 72+x=-23 | | 2p+3=5(1-4p)/7 | | 10x+22=8x−14 | | 10000=12.56(h) | | (2y+1)/5=3 | | 5-4(3-2p)=4p-5 | | 10=12.56(h) | | 1x^2-0,5+0=0 | | 2.25x^2+4x=0 | | 9c|24=3 | | x+3x5=24 | | 4{s}^{3}+15{s}^{2}+18s+5=0 | | X^2+22x=-96 | | 15x^2-14x+21=0 | | 3x/4-3/2=x/3-6/5 | | √|x|^2=x | | 14x=9=131 | | 4(x+3)+5x=x-12 |